Acyl-coenzyme A binding protein MoAcb1 regulates conidiation and pathogenicity in Magnaporthe oryzae - Cao, Na; Zhu, Xue-Ming; Bao, Jian-Dong; Zhu, Li-Hong; Liu, Hao; Lin, Fu-Cheng; Li, Lin (Frontiers in Microbiology, 2023)
Magnaporthe oryzae is a filamentous fungus that causes rice blast. Rice blast seriously threatens the safety of food production. The normal synthesis and metabolism of fatty acids are extremely important for eukaryotes, and acyl-CoA is involved in fatty acid metabolism. Acyl-CoA binding (ACB) proteins specifically bind both medium-chain and long-chain acyl-CoA esters. However, the role of the Acb protein in plant-pathogenic fungi has not yet been investigated. Here, we identified MoAcb1, a homolog of the Acb protein in Saccharomyces cerevisiae. Disruption of MoACB1 causes delayed hyphal growth, significant reduction in conidial production and delayed appressorium development, glycogen availability, and reduced pathogenicity. Using immunoblotting and chemical drug sensitivity analysis, MoAcb1 was found to be involved in endoplasmic reticulum autophagy (ER-phagy). In conclusion, our results suggested that MoAcb1 is involved in conidia germination, appressorium development, pathogenicity and autophagy processes in M. oryzae.